2021
DOI: 10.1021/acssuschemeng.1c04272
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Doped Highly Dispersed RuO2 Catalyst with Abundant Oxygen Vacancies for Efficient Decarboxylation of l-Lysine to Cadaverine

Abstract: Chemical decarboxylation of l-lysine is a promising route for producing cadaverine, which is the key monomer of new polyamide, polyurethane, and nylon materials. Currently, the wide application of Ru-based catalysts is restricted by its low efficiency which was mainly caused by the severe agglomeration of ruthenium nanoparticle. In this study, manganese (Mn) doped ruthenium oxide catalyst was synthesized through the wetness impregnation method with Beta zeolite as the candidate support for efficient decarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Our previous work showed that active surface oxygen vacancies in catalysts facilitated the adsorption of intermediate in the decarboxylation of L-lysine [13]; therefore, the relationship between the quantity of oxygen vacancies in catalysts and their catalytic performances were studied. The high-resolution O 1s spectra for RuO 2 @FAU, RuO 2 @FAU-12 and RuO 2 @FAU-NH 4 -3 catalyst were depicted in Figure 7A-C.…”
Section: Enhanced Performance In Decarboxylation Of L-lysine To Cadav...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work showed that active surface oxygen vacancies in catalysts facilitated the adsorption of intermediate in the decarboxylation of L-lysine [13]; therefore, the relationship between the quantity of oxygen vacancies in catalysts and their catalytic performances were studied. The high-resolution O 1s spectra for RuO 2 @FAU, RuO 2 @FAU-12 and RuO 2 @FAU-NH 4 -3 catalyst were depicted in Figure 7A-C.…”
Section: Enhanced Performance In Decarboxylation Of L-lysine To Cadav...mentioning
confidence: 99%
“…Products were determined using LC-UV (Waters) equipped with a C18 column (100 Å, 5 µm, 4.6 mm × 250 mm) according to the method described in our previous work [13]. To be brief, 50 µL of the diluted solution and 50 µL of dansyl chloride (5 mg/mL in acetone) were successively added into a 4 mL centrifuge tube, and the mixture was heated by ultrasonic pretreatment for 10 min in the dark.…”
Section: Evaluation In Decarboxylation Of L-lysine To Cadaverinementioning
confidence: 99%
See 1 more Smart Citation
“…), and create unique synergistic effects and interactions between elements. 19,20 Appropriate element doping can provide an effective route to improve oxygen activation capacity. 21,22 Among them, Ce-doped metal oxide catalysts exhibit good catalytic oxidation performance, which can be ascribed to their unique amphoteric properties, and to the Ce 4+ /Ce 3+ redox pair.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Doping metal oxide with another element can change lattice parameters, generate additional active sites (defects, vacancies, etc. ), and create unique synergistic effects and interactions between elements. , Appropriate element doping can provide an effective route to improve oxygen activation capacity. , Among them, Ce-doped metal oxide catalysts exhibit good catalytic oxidation performance, which can be ascribed to their unique amphoteric properties, and to the Ce 4+ /Ce 3+ redox pair. Therefore, a cerium-doped manganese oxide may create a unique synergy between Mn and Ce, greatly enhancing their oxygen activation ability, realizing the replacement of H 2 O 2 with O 2 (or atmospheric oxygen) as the oxidant …”
Section: Introductionmentioning
confidence: 99%